Desain Strategi Kolaborasi Antara Lembaga Pengembangan Bahasa Arab: Tinjauan Konseptual Sebagai Upaya Dalam Meningkatkan Partisipasi Peserta Nadwah Usbu’iyyah di IAIN Palopo - Urmila Rahmadani; Naidin Syamsuddin; Mustafa Mustafa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The low participation of participants in Nadwah Usbuiyyah is caused by a lack of encouragement and ineffective management of activities. Therefore, the researcher proposes collaboration between Arabic language development institutions to exchange ideas and formulate concrete steps in creating innovative solutions. This study aims to develop a collaborative strategy design as an effort to increase the participation of participants in Nadwah Usbu’iyyah at IAIN Palopo. The involved institutions include the Language Development Unit, the Arabic Language Education Study Program, and the Student Association of the Arabic Language Education Study Program. The method used is Research & Development (R&D) with the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation, conducted from August to September 2024. Data collection techniques include interviews, Focus Group Discussions (FGD), and documentation. The results indicate the validity level of the collaborative strategy design by language validators at 89% and content validators at 93%, both categorized as very valid. The FGD assessment also shows a feasibility rate of 91%, indicating that this strategy design is highly suitable for implementation in Nadwah Usbuiyyah activities.